2015
DOI: 10.1007/s40265-015-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Development of Antineoplastic Agents Derived from Natural Products

Abstract: Through years of evolutionary selection pressures, organisms have developed potent toxins that coincidentally have marked antineoplastic activity. These natural products have been vital for the development of multiagent treatment regimens currently employed in cancer chemotherapy, and are used in the treatment of a variety of malignancies. Therefore, this review catalogs recent advances in natural product-based drug discovery via the examination of mechanisms of action and available clinical data to highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 248 publications
(239 reference statements)
1
27
0
Order By: Relevance
“…We found that euphol treatment exhibited dose-dependent cytotoxic effects on all tested glioma cancer cell lines. In agreement with our recent study, the IC 50 values presented were lower than 30 μg /mL for 72 h, a criterion adopted by NCI to consider an extract as promising for preclinical studies (http://www.cancer.gov) [33]. The mean of IC 50 values was 19.38 μM (8.28 μg/mL).…”
Section: Discussionsupporting
confidence: 90%
“…We found that euphol treatment exhibited dose-dependent cytotoxic effects on all tested glioma cancer cell lines. In agreement with our recent study, the IC 50 values presented were lower than 30 μg /mL for 72 h, a criterion adopted by NCI to consider an extract as promising for preclinical studies (http://www.cancer.gov) [33]. The mean of IC 50 values was 19.38 μM (8.28 μg/mL).…”
Section: Discussionsupporting
confidence: 90%
“…Many antineoplastic drugs are derived from natural products: synthetic and medicinal chemistry therefore plays a central role in the process leading to marketed drugs [80]. Homoharringtonine ( Figure 4A, compound 1) is a cephalotoxine ester that was discovered in 1963 from Cephalotaxus harrigtonia, including cephalotaxine (compound 2), isoharringtonine (compound 3) and harringtonine (compound 4) [81].…”
Section: Homoharringtonine a Clinically Used Ribosome Inhibitormentioning
confidence: 99%
“…Naturally occurring dietary compounds derived from medicinal plants serve important roles against inflammation and cancer (1)(2)(3). Coffee, the most commonly consumed beverage worldwide, is a rich source of dietary phenolic phytochemicals (4).…”
Section: Introductionmentioning
confidence: 99%